Pengaruh Kepemimpinan Terhadap Kepuasan Kerja Guru Pada SMK Muda Pekanbaru - Yayang, Yayang; iskandar, iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The objective of this study is to examine The Influence of Leadership on Teacher Job Satisfaction at SMK MUDA Pekanbaru. The research population consisted of all teachers at SMK MUDA Pekanbaru during the 2023/2024 academic year, totaling 60 individuals. The research sample comprised 59 respondents. The research methodology employed in this study utilized descriptive and quantitative methods, subsequently analyzed using simple linear regression analysis. The descriptive data analysis results revealed that the mean value for the Leadership variable was 3.94, indicating that respondents' answers to all Leadership statements were categorized as